(untitled) (Journal of Environmental Science and Natural Resources, 2017)
Phenotypic screening of existing 10 familiar landraces performed at germination and seedling stages and their molecular characterization were conducted at Bangladesh Institute of Nuclear Agricultural (BINA) during the period of December 2014 to May 2015 to screen out better cold tolerant genotypes among 10 landraces where one susceptible, two moderately tolerant and two tolerant BRRI released varieties were used as check genotypes. The present study evaluated several parameters at the germination stage after 7 days of germination and at the seedling stage after 28 days of seedling growth for phenotypic screening. Modified hydroponic method was used at the seedling stage and the temperature treatments were maintained artificially at 15°C and 25°C respectively. Polymorphic microsatellite or SSR markers were selected for molecular characterization showing that attributes were positively regulated due to cold stress in BRRIdhan 36, LR 114- Badiabona and LR 54- Tor Balam. The findings of genetic diversity analysis for landraces LR 114- Badiabona and LR 54- Tor Balam appeared to resemble to that of tolerant genotype BRRIdhan 36. Based on phenotypic screening and UPGMA dendrogram study, landraces LR 114- Badiabona and LR 54- Tor Balam appeared superior as genetic material. Better cold tolerant rice variety may be developed from further breeding process. J. Environ. Sci. & Natural Resources, 10(1): 85-91 2017